The spatial impact of a Western diet in enriching Galectin-1-regulated Rho, ECM, and SASP signaling in a novel MASH-HCC mouse model - Tahereh Setayesh; Ying Hu; Farzam Vaziri; Dongguang Wei; Yu-Jui Yvonne Wan (BMC, 2024)
Abstract Background Hepatocellular carcinoma (HCC) arising from metabolic dysfunction-associated steatohepatitis (MASH) presents a significant clinical challenge, particularly given the prevalence of the Western diet (WD). The influence of diet on the tumor microenvironment remains poorly understood. Galectin-1 (Gal-1) is a biomarker for HCC and has a crucial role in liver carcinogenesis. Our previous studies demonstrated that silencing Gal-1 effectively treats mouse HCC. However, the impacts of a WD on Gal-1 signaling on MASH to HCC progression are unknown, and this study addresses these knowledge gaps. Methods We developed a novel MASH-HCC mouse model. Using spatial transcriptomics and multiplex immunohistochemistry (IHC), we studied the effects of a WD on the liver and tumor microenvironment. By modulating Gal-1 expression through silencing and overexpression, we explored the location-specific impacts of WD on Gal-1 signaling. Results Pathways such as Rho signaling, extracellular matrix (ECM) remodeling, and senescence-associated secretory phenotypes (SASP) were prominently activated in WD-induced metabolic dysfunction-associated fatty liver disease (MAFLD) and MASH-HCC, compared to healthy livers controls. Furthermore, Rho GTPase effectors, ECM remodeling, neutrophil degranulation, cellular stress, and cell cycle pathways were consistently enriched in human and mouse MASH-HCC. Spatially, these pathways were enriched in the tumor and tumor margins of mouse MASH-HCC. Additionally, there was a notable increase in CD11c and PD-L1-positive cells from non-tumor tissues to the tumor margin and inside the tumor of MASH-HCC, suggesting compromised immune surveillance due to WD intake. Moreover, MASH-HCC exhibited significant Gal-1 induction in N-Cadherin-positive cells, indicating enhanced epithelial-to-mesenchymal transition (EMT). Modulating Gal-1 expression in MASH-HCC further established its specific roles in regulating Rho signaling and SASP in the tumor margin and non-tumor tissues in MASH-HCC. Conclusion WD intake significantly influences vital cellular processes involved in Gal-1-mediated signaling, including Rho signaling and ECM remodeling, in the tumor microenvironment, thereby contributing to the development of MASH-HCC.